Editorial - Miguel, Paulo A. Cauchick (Brazilian Journal of Operations & Production Management, 2010)
On behalf of the Editorial Board, I am happy to deliver the second issue of volume 2 (2005) of the Brazilian Journal of Operations & Production Management. We appreciate all the people who support and contribute to the editorship. The accomplishment of this issue would not be possible without the work of our editorial review board. As always, we would like to take this opportunity to acknowledge them due to their contribution to the authors and to the journal referral process. We hope the readers fi nd the articles in this issue a useful source within the scope of production engineering and operations management. Please enjoy them.